2020
DOI: 10.1007/s00395-019-0772-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective intrarenal delivery of mesenchymal stem cell-derived extracellular vesicles attenuates myocardial injury in experimental metabolic renovascular disease

Abstract: Background: Extracellular vesicles (EVs) deliver genes and proteins to recipient cells, and mediate paracrine actions of their parent cells. Intrarenal delivery of mesenchymal stem cell (MSC)-derived EVs preserves stenotic-kidney function and reduces release of pro-inflammatory cytokines in a swine model of coexisting metabolic syndrome (MetS) and renal artery stenosis (RAS). We hypothesized that this approach is also capable of blunting cardiac injury and dysfunction.Methods: Five groups of pigs were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…For EV characterization, 12 three-months-old female domestic pigs (Manthei Hog Farm, Elk River, MN) were observed for 16 weeks in two groups. Control pigs (Lean) were fed a standard chow (13% protein, 2% fat, 6% fiber, Purina Animal Nutrition LLC, MN), and MetS pigs a metabolic-atherosclerotic diet (5B4L, protein 16.1%, ether extract fat 43.0%, and carbohydrates 40.8%, Purina Test Diet, Richmond, IN) ( n = 6 each) [ 17 ]. After completion of diet, systemic parameters including body weight, blood pressure (measured with an intra-arterial catheter), and venous levels of cholesterol, triglycerides, fasting glucose, and insulin were measured by standard procedures [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For EV characterization, 12 three-months-old female domestic pigs (Manthei Hog Farm, Elk River, MN) were observed for 16 weeks in two groups. Control pigs (Lean) were fed a standard chow (13% protein, 2% fat, 6% fiber, Purina Animal Nutrition LLC, MN), and MetS pigs a metabolic-atherosclerotic diet (5B4L, protein 16.1%, ether extract fat 43.0%, and carbohydrates 40.8%, Purina Test Diet, Richmond, IN) ( n = 6 each) [ 17 ]. After completion of diet, systemic parameters including body weight, blood pressure (measured with an intra-arterial catheter), and venous levels of cholesterol, triglycerides, fasting glucose, and insulin were measured by standard procedures [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Abdominal subcutaneous adipose tissue collection, MSC isolation and culture, and EV collection were performed as previously described [17].…”
Section: Mscs and Ev Harvestingmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of IA therapeutics for kidney disease, however, relies on the availability of animal models and feasibility of surgical techniques. Previous studies that injected MSCs directly into the renal artery have used larger animal models, including cats [23], pigs [24], rats [25], and sheep [26]. Indeed, a meta-analysis of 21 studies applying MSC therapy to animal models of renal failure has suggested that IA delivery of MSCs has greater therapeutic effect compared to intravenous delivery [27]; it should be noted though that the studies used different animal and disease models, and none of them did a direct comparison between delivery routes.…”
Section: Discussionmentioning
confidence: 99%